Expert F# 2.0 - Syme, Don; Cisternino, Antonio; Granicz, Adam (Apress, 2008)
Expert F# 2.0 is about practical programming in a beautiful language that puts the power and elegance of functional programming into the hands of professional developers. In combination with .NET, F# achieves unrivaled levels of programmer productivity and program clarity.